The tone of the narratives about risk in the value creation of Portuguese listed companies - Oliveira, G. M.; Azevedo, G.; Oliveira, J. (International Women's Day Conference in Economics, Finance and Management, 2021)
Globalization, corporate fraud scandals and the complexity of risks are some of the aspects that have intensified companies' search for effective alternatives for risk control and management. Factors such as these have also attracted investors' detailed attention to the information issued by companies in their annual reports, setting expectations on the organization's financial, economic and social performance. Thus, due to the importance of management reports in the decision-making of the various Stakeholders and taking into account the existence of informative content in the feeling of managers when transmitting the message to interested parties, this study aims to analyze the effects of the tone of the risk narratives on companies’ value. To this end, we explored the risk reports for 2018 of the Portuguese non-finance listed. Findings indicate that the tone used in the risk reports is associated with the company's value and that the more prominent the use of words that characterize "Activity", the lower the business value.